Approximating Fixed Points of Enriched Nonexpansive Mappings in Geodesic Spaces. (4th May 2022) - Shukla, Rahul; Panicker, Rekha
Abstract : In this paper, we consider the class of enriched nonexpansive mappings in the setting of geodesic spaces. We obtain a number of fixed point theorems for these mappings in geodesic spaces. Further, we employ the SP iterative method and present some new convergence theorems for the class of enriched nonexpansive mappings under different assumptions. We present some results concerning Δ and strong convergence.